Penelusuran Nilai Filosofis Peninggalan Warisan Kesultanan Buton di Keraton Buton Kota Baubau - Jasrudin, Jasrudin; Ramly, Amisbah; Arni, Arni; Ramadani, Sahra (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
This research examines the philosophical values of the Buton Sultanate heritage in the Buton Palace, Baubau City. The aim of this research is to explore and document the philosophical values contained in the heritage of the Buton Sultanate in the Buton Palace, Baubau City. The method used is a qualitative method with a descriptive-exploratory approach, The data obtained was analyzed using the thematic analysis method, namely interview data and observation. The research results show that Masigi Ogena, Wolio Fort, Popua Rock, Yi Gandangi Rock, and Sultan Murhum's Tomb not only function as historical artifacts, but also as important symbols of spirituality, justice, leadership, and togetherness. These values play a role in shaping the cultural and social identity of the Butonese people and have strong relevance in the modern era, especially in the context of character education, cultural tourism and heritage preservation efforts.